AN ANALYSIS OF FIGURATIVE LANGUAGE USED BY PARENTS IN EDUCATING THEIR CHILDREN IN WANGI-WANGI SUB-DISTRICT WAKATOBI REGENCY - Adu, Baharudin; Nety, Nety; Jimiludin, Jimiludin (English Education Department, 2023)
The problem statement in this research are what figurative language do parents often use at Wangi-Wangi Sub-district, Wakatobi Regency in educating their children?, what figurative language that most used by parents in the Wangi-Wangi Sub-district, Wakatobi Regency in educating their children? and why parents prefer figurative language than common language when educating their children in Wangi-Wangi Sub-District, Wakatobi Regency. The objective of this research are find out the kinds of figurative language used by parents to educate their children in Wangi-Wangi Sub-district, Wakatobi Regency, to find out that most figurative language used by parents in Wangi-wangi sub-district, Wakatobi Regency in educating their children and to find out why parents used figurative language to educating their children in Wangi-Wangi Sub-District Wakatobi Regency.This research used a qualitative design with the qualitative descriptive method. The subjects of this research were parents, custom village and children in Wangi-Wangi Sub-district, Wakatobi Regency. Instrument and technique of data collection in this research used interview, observation and documentation and technique of data analysis in this research was based on [1] model namely, reduction, display and verification.The results of this research indicate that there are 37 figurative languages and 8 types of figurative language were still frequently used by parents, custom village in educating their children and which children hear in Wangi-Wangi District, Wakatobi Regency. Namely metaphor, simile, irony, oximoron, hyperbole, personification, epithet and metonym. Of the 37 figurative languages used there are 18 figurative languages used by parents, 9 which are often used by custom village and 10 which children hear from their parents. The figurative language most often used by parents in Wangi-Wangi Sub-district, Wakatobi Regency is simile with a total of 10 Simile, 7 metonym, 6 Irony, 5 Metaphors, 3 Oxymoron, 3 Hyperbole, 2 personification, and 1 epithet. Parents choose figurative language in educating their children because the language used is softer and children are not easily offended.